The Relationship Between Airway Antioxidant Levels, Alcohol Use Disorders, and Cigarette Smoking - Burnham, Ellen L. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Alcohol use disorders (AUDs) and cigarette smoking are associated with pulmonary oxidative stress, likely related to antioxidant depletion. Pulmonary oxidative stress may adversely affect innate immunity, leading to increased pneumonia susceptibility and severity, including development of the acute respiratory distress syndrome. In people with AUDs, most of whom smoke, antioxidant therapy can potentially restore immune cell function and attenuate pneumonia development. Challenges to human investigations of antioxidant therapies include an inability to identify pulmonary oxidative stress noninvasively and the optimal route to deliver pulmonary antioxidants. We sought to determine whether bronchoalveolar lavage (BAL) measures of thiol antioxidants from a 50-ml upper airway aliquot approximated those in the alveolar space and to determine whether AUDs and/or smoking affected these relationships. METHODS: Healthy human subjects with and without AUDs, including smokers and nonsmokers, underwent BAL. Samples obtained after the first 50-ml normal saline aliquot were analyzed as representing bronchial airways; subsequent 50-ml aliquots were analyzed as representative of the alveolar space. Reduced and oxidized (GSSG) glutathione, cysteine (Cys), and its oxidized species, cystine, along with mixed disulfides (MDs) were quantified using high-performance liquid chromatography. The percent of total thiols present in their oxidized forms, and thiol redox potentials, were calculated. RESULTS: Positive correlations between upper and lower BAL fluid thiol species were observed that were most robust for GSSG (ρ = 0.85), Cys (ρ = 0.83), and MDs (ρ = 0.69), but poor for thiol redox potential measures. In contrast to nonsmokers (either with or without AUDs), in subjects with AUDs who smoked, upper BAL fluid %GSSG, Cys, and MD measures were relatively increased compared to lower. CONCLUSIONS: A small volume BAL procedure may be suitable to assess intrapulmonary oxidative stress related to thiol depletion. Factors including AUDs and smoking may disproportionately increase upper airways oxidative stress that could be relevant for therapeutic interventions.